THE EMOTIONAL INFECTION OF THE VIRTUAL INNOVATION PROJECT TEAM - S. Bushuyev; N. Bushuyeva; V. Bushuieva (Scientific Journal of Astana IT University, 2020)
Emotional infection is considered as a social and psychological mechanism of transferring the mental mood of the manager to the virtual project team and stakeholders of the projects. Emotional impact in the face of direct contact and the inclusion of the virtual team members in certain mental states have an impact on the effectiveness of project management. The main objective of emotional infection analysis is educated and creates the organization of new behavior in adverse, deadly, and aggressive external conditions the manager or virtual team. In times of global crisis and depression 2.0, the emotional behavior of the innovation project manager and his infection with the project team is exacerbated by external uncertainty. The stakeholder infection model is based on an understanding of the life cycle of the project manager, which is presented as a curve for personal changes of the manager of innovative communication projects and programs. Emotions are considered in content, reflecting the various aspects and meanings that caused them. To apply the psychophysiological formula for assessing the impact of the emotional state of the virtual team of innovative projects, these influences have been transformed into a competent model for managing these projects.